Effectiveness of breast milk substitute marketing code education on breastfeeding mothers’ knowledge and self-efficacy - Putri Widita Muharyani; Nurna Ningsih; Karolin Adhisty; Herliawati Herliawati; Yodias Gloria Kusuma Putri; Suwarsi Suwarsi (Universitas Aisyiyah Yogyakarta, 2026)
Exclusive breastfeeding during the first 6 months of life is essential for infant health, yet coverage remains low worldwide. The International Code of Marketing of Breast-milk Substitutes (BMS Code) was developed to protect breastfeeding from inappropriate formula promotion. This study aimed to examine the effect of education about the BMS Code on breastfeeding mothers’ knowledge and self-efficacy. A one-group pretest–posttest design was conducted among 88 breastfeeding mothers selected through purposive sampling in the working area of the Sako Community Health Center, Palembang, Indonesia. Data were collected using a validated questionnaire with acceptable reliability. Knowledge changes were analyzed using the marginal homogeneity test, while changes in self-efficacy were assessed using the McNemar test. The proportion of mothers with good knowledge increased from 3.4% before the intervention to 52.3% after the intervention. High self-efficacy also increased from 53.4% to 86.4%. Significant improvements were found in both knowledge and self-efficacy after the intervention (p < 0.001). Education on the BMS Code effectively improved breastfeeding mothers’ knowledge and self-efficacy and may help mothers recognize inappropriate formula marketing and make more informed breastfeeding decisions. Future studies should use larger samples, stronger experimental designs, and extend the follow-up period to determine whether the intervention effects can be maintained over time.